Product innovation effect on consumer's perceptions - Lucian-Florin Onişor; Mihai-Ioan Roşca (The International Journal of Management Science and Information Technology (IJMSIT), 2013)
Romanian market, as a developing marketplace is plundered with products created by latest scientific discoveries or innovative technologies of the moment. The purpose of this article is to explore the perception of Romanian consumers among innovative technologies products. The novelty characteristics of new product innovations may stimulate users to accommodate the product to other uses, derived from the original ones or not. Different studies about new products acceptance on the market are carried out by specialists from various fields of activity but the focus of this paper is to clarify how are perceived those products by consumers from the marketing point of view. Marketing science can inhibit or accelerate the rhythm of innovations that are being introduced on the market, by preparing absorption of new products in more or fewer stages. After reviewing the literature, it is presented an exploratory type research, based on a survey data collecting information. The findings of the study indicate that Romanian consumers has little concern about latest innovations, but they wants, in the same time, to solve day-to-day life problems that they face, in previously unattempt fashions. The study is among the first in this field and is still in the preliminary phase for the consolidation of new theories that are to be validated by building a scientific economical-statistical-mathematical model to anticipate customer response to a product that utilizes an absolutely different technology.
Keywords: 650; innovation; marketing; consumers' perception; innovative technologies products; Romania